ANALYSIS OF PRICING STRATEGIES AND CONSUMER BEHAVIOUR IN THE CONTEXT OF MARKETING RESEARCH (Economic journal of Lesya Ukrainka Volyn National University, 2024)
Abstract introduction. The article examines the views of scientists regarding the formation of price strategies. The main approaches to pricing are considered, with the help of which companies set optimal prices for their services and goods. Factors affecting the company's choice of pricing strategy and affecting consumer behavior are considered. It is conducted research in relation to behavior of consumers and built model of satisfaction of consumer necessities.The purpose of the article. Consideration of pricing strategies of companies and their impact on consumer behavior. Researching consumer behavior and building a model for satisfying consumer needs in goods or services.Methods.  Carrying out research the methods of abstraction, analysis, logical, theoretical and historical generalization and comparison are used. For basis of research a dialectical method is taken.Results.  The article examines the main approaches to pricing, with the help of which companies set optimal prices for their services and goods. The factors affecting the company's choice of price strategy are considered, and the factors influencing consumer behavior are highlighted. Conducted research on consumer behavior. The proposed model of meeting the needs of consumers in goods or services, which contains 8 sections: the consumer's awareness of the need for the need for a product or service; collection of information; selection of goods or services; decision-making; purchase (payment) of goods or services; evaluation of the choice made and enrichment of experience; the degree of satisfaction of the need for a product or service and consumption of the results.Conclusiоns.  After researching and analyzing the available types of marketing price strategies, business entities choose their own price strategy, taking into account certain existing tools, taking into account: characteristics of the service or product, market segment, market competition, competitor analysis, level of market demand, marketing strategies, etc. .. The use of the correct price strategy and the concept of pricing contributes to the achievement of goals: ensuring the stable financial condition of the business entity, meeting the needs of consumers.The offered model in relation to satisfaction of necessities of consumers in commodities or services gives understanding to the process of making decision by consumers in relation to a purchase that is the basic factor of success of company in a competition environment. Companies, that is able to adapt oneself to the necessities of consumers and, to their requirements, that understand the customers, have more chances to retain and attract clients, promote a competitiveness and score a success at the market.The question of the method of determining prices for certain types of services and the behavioral reaction of consumers requires further research.
Keywords: price, pricing policy, marketing, consumer behavior, marketing price policy